GRE and Undergraduate GPA as Predictors of Veterinary Medical School Grade Point Average, VEA Scores and NAVLE Scores While Accounting for Range Restriction - Danielson, Jared A.; Burzette, Rebecca G. (Frontiers in Veterinary Science, 2020)
We explored the relation between Undergraduate GPA (UGPA) and Graduate Record Examination (GRE) Verbal scores and several indices of achievement in veterinary medical education across five cohorts of veterinary students (N per model ranging from 109 to 143). Achievement indices included overall grade point average in veterinary school (CVMGPA), scores on the North American Veterinary Licensing Examination (NAVLE) and scores on the Veterinary Educational Assessment (VEA). We calculated zero order correlations among all measures, and corrected correlations for range restriction. In all cases, corrected correlations exceeded uncorrected ones. For each index of achievement, we conducted hierarchical regressions using the corrected correlations as input, entering UGPA in the first step and GRE Verbal in the second step. Overall, UGPA and GRE Verbal combined explained from 70% to 84% of variance in CVMGPA, 51% to 91% of variance in VEA scores, and 41% to 92% of variance in NAVLE scores. For twelve of fifteen comparisons, the second step (including GRE Verbal scores) significantly improved R2. Our results reaffirm the value of UGPA scores and GRE Verbal scores for predicting subsequent academic achievement in veterinary school.